Update on the pharmacogenetics of NATs: structural considerations. (November 2008) - Stanley, Lesley A; Sim, Edith
The arylamine N -acetyltransferase ( NAT ) genes encode enzymes that catalyze the N -acetylation of aromatic amines and hydrazines and the O -acetylation of heterocyclic amines. These genes, which play a key role in cellular homeostasis as well as in gene––environment interactions, are subject to marked pharmacogenetic variation, and different combinations of SNPs in the human NAT genes lead to different acetylation phenotypes. Our understanding of the consequences of pharmacogenetic variability in NATs has recently been enhanced by structural studies showing that effects on protein folding, aggregation and turnover, as well as direct changes in active site topology, are involved. These developments pave the way for a better understanding of the role played by NATs in maintaining cellular homeostasis. In addition, the NATs represent a model for studying fundamental processes associated with protein folding and pharmacogenomic effects mediated by inheritance in human populations across a polymorphic region of the genome.